Reference and information services in selected Philippine academic libraries: Trends and future prospects - Fresnido, Ana Maria B. (Animo Repository, 2015)
With the steady decrease in face-face reference transactions, Philippine libraries have accepted the challenge to embrace Reference 2.0 tools and be one with their clients in finding and providing information electronically. New reference service models have likewise emerged in view of further improving reference and information services that would respond to the changing needs of library patrons. While the pace of change has been rather slow, it has surely brought patrons and librarians to a higher plane in as far as the new information environment is concerned. To gather information on the current trends and future directions of reference and information services in Philippine academic libraries, the libraries of the top universities in the country included in the Quacquarelli Symonds (QS) Asian University Rankings namely, the University of the Philippines (UP) (ranked as number 68), Ateneo de Manila University (ADMU) (ranked as number 86), the De La Salle University (DLSU) (ranked as number 142), the University of Santo Tomas (UST) (ranked as number 148) and the University of Southeastern Philippines (USeP) (ranked as number 251-300) were surveyed The survey questionnaire focused on the use of different reference service models as well as Reference 2.0 tools, adoption of emerging trends in reference and information services, future plans, and issues encountered in the process of introducing changes in the way they render said services. The instrument was distributed to the head librarians of the sample being studied through email and/or Facebook (private message). Accomplished survey questionnaires were compiled and analyzed using descriptive statistics. Results of the survey revealed that while a number of new service models are currently being implemented in most of the surveyed libraries simultaneously, they remained very cautious in introducing models that will completely rid of the traditional reference desk. Likewise, despite the wide acceptance of virtual reference, the libraries have not taken full advantage of the use of Reference 2.0 tools primarily because they have to wrestle with staff competency issues.